Rancang Bangun Sistem Pemantauan Kadar Air dan Suhu Tanah Otomatis Berbasis IoT - Adrian Renaldi Rachmat; Mohammad Attar Gibran; Afif Izaaz; Neil Farel Rindra Tempo; Gabrielle Luoise Abraham (Jurnal Otomasi Kontrol dan Instrumentasi, 2026)
Modernization of meteorological observation systems at the Agency for Meteorology, Climatology, and Geophysics (BMKG) is necessary, particularly for soil temperature and soil water content parameters that are still commonly measured using conventional methods. This study presents the design and evaluation of an Internet of Things (IoT)-based monitoring system to improve observation efficiency. The system integrates PT100 sensors to measure soil temperature at depths of 5, 10, 20, 50, and 100 cm, and Capacitive Soil Moisture v2.0 sensors to measure volumetric soil water content at depths of 10, 20, 30, 50, and 100 cm. Data is transmitted in real time via Wi-Fi to Google Spreadsheet and a Telegram bot, enabling remote monitoring and automatic notifications, while also being stored locally on an SD card for reliability. Sensor performance was evaluated through laboratory calibration in a temperature chamber and an 11-day field deployment at the BMKG Regional II Headquarters. Results show good accuracy, with RMSE of 0.93 °C (MAE 0.66 °C) at 5 cm depth and RMSE of 0.43 °C (MAE 0.29 °C) at 10 cm depth, demonstrating reliable system performance.